2019
DOI: 10.1111/1744-7917.12711
|View full text |Cite
|
Sign up to set email alerts
|

Identification and temporal expression profiles of cuticular proteins in the endoparasitoid wasp, Microplitis mediator

Abstract: Recently, parasitoid wasp species Microplitis mediator has evoked increasing research attention due to its possible use in the control of Lepidoptera insects. Because insect development involves changes in cuticle composition, identification and expression analysis of M. mediator cuticular proteins may clarify the mechanisms involved in parasite development processes. We found 70 cuticular proteins from the M. mediator transcriptome and divided them into seven distinct families. Expression profiling indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 96 publications
(161 reference statements)
0
13
0
Order By: Relevance
“…Hierarchical clustering analysis indicated that six clusters of CP genes with dynamic expression profiles were strikingly observed across developmental stages. Stage-specific expression of CP genes was also detected in other insects, such as Microplitis mediator, Bactrocera dorsalis, Dendrolimus punctatus and Nilaparvata lugens [14,31,34,35]. During larval to pupal development of FAWs, the expression pattern of the majority of CP genes had major changes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Hierarchical clustering analysis indicated that six clusters of CP genes with dynamic expression profiles were strikingly observed across developmental stages. Stage-specific expression of CP genes was also detected in other insects, such as Microplitis mediator, Bactrocera dorsalis, Dendrolimus punctatus and Nilaparvata lugens [14,31,34,35]. During larval to pupal development of FAWs, the expression pattern of the majority of CP genes had major changes.…”
Section: Discussionmentioning
confidence: 82%
“…Few CP genes were abundant in nearly all life stages, suggesting a significant role in general cuticle synthesis. It was documented that CP genes that displayed the most abundant expression in specific tissue at particular developmental stages played important roles associated with such tissues during specific developmental periods [12,14,24,31,33,34]. Thus, further investigation into unravelling the expression of CP genes between premolt/eclosion and post-molt/eclosion at particular developmental stages and multiple tissues is essential to provide deep insights into the functional perspectives of CPs in FAW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins associated with HearNPV BVs and ODVs have been identified (Hou et al ., 2013). In our previous studies, the immune system of H. armigera and its interaction with exogenous biological factors have also been studied (Xiong et al ., 2015; Volovych et al ., 2019; Du et al ., 2020; Lin et al ., 2020; Wang et al ., 2020), and the immune mechanisms of the in vivo systemic phase of BV infection were revealed in H. armigera fat body and hemolymph (Xing et al ., 2017; Yuan et al ., 2017). Since midgut is the primary infection site of baculovirus (Wang & Hu, 2019), it is reasonable to predict that gut microbiota may play a role in baculovirus infection by modulating host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Double‐stranded RNAs (dsRNAs) were synthesized as previously described (Volovych et al ., 2020; Wang et al ., 2019). Briefly, the sense and antisense primers were designed to generate cDNA fragments of MaGal2 by PCR.…”
Section: Methodsmentioning
confidence: 99%